Analisis Konsep Haq Al-Ta’lif dan Relevansinya dengan Perlindungan Hak Kekayaan Intelektual (Studi Pemikiran Wahbah al-Zuhaili) - Chuzaimatus Saadah (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
This article discuss the thought of Wahbah al-Zuhaili-as a representation of a personjurist-on intellectual property rights. In Indonesia, violations of intellectual property rights continue to occur even after laws and regulations have regulated them. Even some religious groups consider that plagiarism of written works is permissible in religion. Even though Islam itself regulates and maintains individual rights in such a way through the concept of property rights. Islamic law in the early period did not mention intellectual property rights directly. Wahbah al-Zuhaili in his work discussed haq al-ta’lif (the right of a work). Therefore, to analyze this, the researcher used a library research method with a normative approach. Researcher found that the relevance of the concept haq al-ta'lif with the protection of Intellectual Property Rights in general is first, intellectual property rights recognized by law are protected personal rights advice' even when a country's laws do not provide for it. Second, plagiarizing and disseminating (commercializing) without the rights owner's permission is tyranny which is a vice. Third, the owner of the right has the right to confiscate and stop the production of the perpetrators. Fourth, the owner of the right is entitled to compensation for moral and material losses for the stolen work. Fifth,a work can be used by other parties with the existence of an agreement on a certain object with a specified time.